2021
DOI: 10.3390/brainsci11030396
|View full text |Cite
|
Sign up to set email alerts
|

Association between Previous Statin Use and Alzheimer’s Disease: A Nested Case-Control Study Using a National Health Screening Cohort

Abstract: A number of studies report the incidence of Alzheimer’s disease (AD) in patients taking statins, but the results are inconsistent. (1) Background: The present study investigated the cross-sectional association between previous statin use and the risk of AD development in Korean residents. (2) Methods: We used the Korean National Health Insurance Service-National Sample Cohort; 17,172 AD patients were matched by age, gender, income, and region of residence with 68,688 control participants at a ratio of 1:4. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 22 The role of statin treatment to prevent AD is, however, controversial. 22 Once genetically diagnosed, patients with FH receive high-intensity statins. 10 We have previously reported that 86% of Norwegian patients diagnosed with FH are treated with statins.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The role of statin treatment to prevent AD is, however, controversial. 22 Once genetically diagnosed, patients with FH receive high-intensity statins. 10 We have previously reported that 86% of Norwegian patients diagnosed with FH are treated with statins.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there are concerns concerning the reliability of AD diagnosis, which may be somewhat compromised because the diagnosis of AD depends on the disease codes in the database. However, as described in our previous work, we demonstrated that the coding of AD from the National Health Insurance Service Health Screening Cohort data had suitable validity for clinical AD diagnosis [33]. Third, most studies reporting these associations have considered that periodontitis is one of the major sources of tooth loss, which contributes to the enhancement of neuroinflammatory progression in the brain and ultimately results in cognitive impairment [34].…”
Section: Discussionmentioning
confidence: 54%
“…Thus, we were able to adjust for plausible confounding factors and perform stratified subgroup analyses to identify potentially relevant interactions. Although the diagnosis of AD was based on ICD-10 coding, the coding of AD from NHIS data had good accuracy and validity, as described in our previous literature ( 18 , see File S2 ). We calculated the interaction for each relationship between the independent variables and basic demographics including age, sex, income, and region of residence in model 2 ( Table S3 ).…”
Section: Discussionmentioning
confidence: 94%
“…Participants who received treatment with levothyroxine for more than 3 months or who had goiter, hypothyroidism, thyroiditis, or hyperthyroidism were evaluated as described previously ( 17 ), and these conditions were included as independent variables. Participants with AD, which was used as the dependent variable in our analysis, were assessed and included as reported in our previous work ( 18 ).…”
Section: Methodsmentioning
confidence: 99%